The CXCL Family Contributes to Immunosuppressive Microenvironment in Gliomas and Assists in Gliomas Chemotherapy - Wang, Zeyu; Liu, Yuze; Mo, Yuyao; Zhang, Hao; Dai, Ziyu; Zhang, Xun; Ye, Weijie; Cao, Hui; Liu, Zhixiong; Cheng, Quan (Frontiers in Immunology, 2021)
Gliomas is a type of malignant central nervous system tumor with poor survival outcome. Novel classifications of gliomas based on gene expression can be applied to predict gliomas patient’s prognosis accurately. Chemokine CXC subfamily plays a critical role in the construction of tumor immune landscape and tumor progression, but its role in gliomas is remain elusive. In this work, samples from TCGA was set as training cohort, while CGGA2, CGGA1, four datasets from GEO database and our own clinical samples were treated as validation cohort. Consensus clustering analysis was first introduced to classified samples based on CXCL expression profile, and the support vector machine was applied to reproduced the cluster model in validation cohort. Next, the elastic net analysis was applied to calculate theriskof each sample based on CXCL expression. High risk samples were associated with more malignant clinical features, worse survival outcome and more complicated immune landscape than low risk samples. Besides, higher immune checkpoint genes expression was also noticed in high risk samples suggesting CXCL may participate in tumor evasive from immune surveillance. Notably, high risk samples also manifested higher chemotherapy resistance than low risk samples. Therefore, we predicted potential compounds which target to high risk samples. Two novel drugs, LCL-161 and ADZ5582, were firstly identified as gliomas potential compounds, and five compounds from PubChem database were filtered out. Taken together, we constructed a prognostic model based on CXCL expression, and predicted that CXCL may affect tumor progression through modulating tumor immune landscape and promoting tumor immune escape. Novel potential compounds were also proposed which may improving gliomas prognosis.